PENGEMBANGAN SISTEM INFORMASI ADMIN UKM SEBAGAI BACKEND PADA E-COMMERCE BERBASIS WEB - Deddy Kusbianto Purwoko Aji Purwoko Aji (STMIK YADIKA BANGIL, 2016)
E-Commerce is a Online Trade Information System, but the reality on the Internet and in the mobile communication network, which is available mostly just contain product display facilities, if there are transaction facilities are still many who apply manual transaction methods, there not using e-banking or m-banking.In this study, will be developed in addition to web-based online trade are equipped with online transactions, on backend also equipped with Accounting Information Systems, thus becoming an integrated UKM Admin management and greatly facilitates the management of e-commerce transactions concerned to handle the distribution of profits, manajemen of data products, and reports generator for UKM AdminKeywords: Accounting Information Systems, E-Commerce, backend, Web